MEASURING THE DEVELOPMENT AND THE USE OF NATIONAL ECONOMY’S INNOVATION CAPACITY - Elena A. Nazarova (Статистика и экономика, 2016)
The article is concerned with the problems of measuring the development and the use of national economy’s innovation capacity. It is clear that innovation capacity of the country is the basis for technical and innovative economic development, it is a strategic resource which enables to achieve competitiveness and sustainable economic growth. Effective national policies in the field of innovation-driven development, in turn, are impossible to pursue without an adequate assessment system which will be proposed in this article.